Merdu puisi the Malay art song album / Khairunnisa Diyana Md Noor, Alia Farahin Abd Wahab and Marzelan Salleh - Md Noor, Khairunnisa Diyana; Abd Wahab, Alia Farahin; Salleh, Marzelan (2022)
This project is a recording of songs in the Art Song genre. Art Song is a composition for voice accompanied by piano and in the style of classical music. First introduced in the 17th century and has been sung in various languages such as in German known as lieder and in French known as Chasons. The use of poetry as a text is very synonymous with the composition of Art Song. In Malaysia, the Art Song genre is still not widely used; therefore, this album, can introduce the Art Song genre to the Malaysian community and increase interest in poetry writing. For this album, a total of 7 Art Song compositions will be recorded. Among the composers involved are Tazul Tajuddin, Alia Farahin and Amanina Alwani. This song with Malay poetry text will be sung by Soprano Khairunnisa Diyana Md Noor with piano accompaniment by Bernard Tan. The songs were chosen to have an image of life and the environment in Malaysia.